Novel taxa of Stenella from forest flora of North-Eastern Uttar Pradesh - P.N. SINGH and S. CHAUDHARY, R.K. CHAUDHARY, M.S. TRIPATHI (Indian Phytopathology, 2002)
This paper is devoted to the description and illustration of four new species of the form genus Stenella viz., S. bischofiae-javanicae, S. browniaeicola, S. caryotae-urensis and S. millettiae occurring on living leaves (in blotches) of Bischofia javanica, Brownea hybrida, Caryota urens and Millettia ovalifolia respectively in forest flora of orth-Eastern Uttar Pradesh, India.